Quantum interference based Boolean gates in dangling bond loops on Si(100):H surfaces - Kleshchonok, Andrii; Gutierrez, Rafael; Joachim, Christian; Cuniberti, Gianaurelio (Giovanni) (Scientific Reports, 2015)
Implementing atomic and molecular scale electronic functionalities represents one of the major challenges in current nano-electronic developments. Engineered dangling bond nanostructures on Silicon or Germanium surfaces posses the potential to provide novel routes towards the development of non-conventional electronic circuits. These structures are built by selectively removing hydrogen atoms from an otherwise fully passivated Si(100) or Ge(100) substrate. In this theoretical study, we demonstrate how dangling bond loops can be used to implement different Boolean logic gates. Our approach exploits quantum interference effects in such ring-like structures combined with an appropriate design of the interfacing of the dangling bond system with mesoscopic electrodes. We show how OR, AND, and NOR gates can be realized by tuning either the global symmetry of the system in a multi-terminal setup - by arranging the position of the input and output electrodes - or, alternatively, by selectively applying electrostatic gates in a two-terminal configuration.
CRIS-Team Scopus Importer:2023-03-20